Kerawanan DBD di Kecamatan Kendal Kabupaten Kendal Tahun 2025 - Jannah, Riskha Khasna Mifhtahul; Alif Noor Anna; Nirma Lila Anggani; M. Iqbal Taufiqurrahman (Mataram University, 2026)
Dengue Hemorrhagic Fever (DHF) remains a public health problem in Kendal District, Kendal Regency, as indicated by fluctuations in the number of cases and mortality rates exceeding World Health Organization standards. This study aims to analyze the vulnerability of DHF in Kendal District in 2025 by integrating environmental and epidemiological factors through a spatial approach. The study used a quantitative descriptive method with spatial analysis. The study population covered the entire Kendal District, while sample locations were determined using a purposive sampling technique to represent variations in vulnerability levels and case incidence. Data were obtained from satellite imagery, spatial data, DHF case data, and field observations. The analysis was conducted using an overlay technique to map vulnerability patterns, then interpreted descriptively to explain the physical and non-physical factors that influence DHF risk. The results showed that the level of DHF vulnerability in Kendal District has spatial variations, where areas with high vulnerability are generally associated with residential density, less than optimal environmental management, and low mosquito breeding control.